2009
DOI: 10.1177/0022034509334070
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Promotes an Odontoblastic Phenotype in Dental Pulp Cells

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. ABSTRACT Dental pulp cells can differentiate toward an odontoblastic phenotype to produce reparative dentin beneath caries lesions. However, the mechanisms involved in pulp cell differentiation under pro-inflammatory stimuli have not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(82 citation statements)
references
References 36 publications
1
78
1
Order By: Relevance
“…8D). Western blotting confirmed expression of DSP, an odontogenic differentiation marker (42), in NHEK/⌬Np63␣-M and DPSC, and absence of the protein expression in NHEK and NHEK/Snail (Fig. 8E).…”
Section: Transduction Of ⌬Np63␣mentioning
confidence: 75%
“…8D). Western blotting confirmed expression of DSP, an odontogenic differentiation marker (42), in NHEK/⌬Np63␣-M and DPSC, and absence of the protein expression in NHEK and NHEK/Snail (Fig. 8E).…”
Section: Transduction Of ⌬Np63␣mentioning
confidence: 75%
“…In a first approach, we demonstrated that the recombinant C-DMP1 polypeptide, mimicking the limited cleavage products obtained by MMP-2, had a profound effect on the differentiation of dental pulp stem/progenitor cells, not observed with the N- polypeptide. Differentiation into putative odontoblast was revealed by the rapid organization of most of the cells into clusters and the increased expression of odontoblast differentiation markers, namely DMP1 and DSPP (Hao et al, 2009, Hao et al , 2004, Paula-Silva et al , 2009). However, as DPSCs are a heterogeneous cell population, further investigations using sorted pulp stem cells will allow us to investigate the mechanism induced by DMP1 derived peptides on pulp cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…83 In the absence of dexamethasone, treatment of osteoprogenitors with TNF-a resulted in dose-dependent increases in ALP activity and mineralized matrix deposition, which are, respectively, early and late markers of osteogenesis. 12,83,[86][87][88] In contrast, when added to dexamethasonecontaining osteogenic medium, TNF-a had the opposite effect on MSCs. 89,90 The pro-regenerative effects of TNF-a seen in dexamethasone-free in vitro MSC cultures were recently confirmed in vivo through repeated injections of TNF-a into a fracture healing model.…”
Section: Tnf-amentioning
confidence: 99%